The Influence of Promotion in Constructing Country's Perception, Autobiographical Memory, Emotional Bonding, and Visiting Intention - Haryanto, Jony Oktavian (The South East Asian Journal of Management, 2009)
This paper aims to propose the influence of promotion toward the establishment of country's perception, autobiographical memory (AM), emotional bonding (EB), and visiting intention. The writer would like to propose the direct influence of promotion toward intention to visit. This paper is aimed to see prospects' perception toward its promotion. Next, the writer would like to explore the influence of country's perception, AM, and EB toward the intention to visit. It is interesting to understand that they function as crucial factors which are considered deeply by prospects before the decide where to go. Hence, it is important to analyze their influence toward intention to visit and including which one is more dominant. This paper proposes 7 hypotheses to analye the relationship above. Data is analyzed using Structural Equation Modelling (SEM) with Lisrel 8.80. The data shows that promotion influences country's perception, AM and EB significantly. On the other hand, emotional bonding influences intention to visit significantly. This research has implications that promotions which are held by countries for tourism should be targeted correctly. Media of promotion or time of promotion have to be analyzed promptly in order to gain effective campaign for prospects. On the other hand, the promotion which is able to create EB or AM has to be developed continuously by tourism industry. Furthermore, marketers need to think appropriate marketing strategies to create a strong emotional bonding between prospects and country.